Perbandingan Hukum Kelembagaan Pertanahan: Badan Pertanahan Nasional di Indonesia dan Het Kadaster di Belanda - Nizam Zakka Arrizal; Siska Diana Sari; Vivi Nanda Prastiwi (Vonis, 2026)
Land administration institutions play a central role in ensuring legal certainty over civil rights attached to land. This article comparatively examines the legal status, legal basis, and institutional structure of the National Land Agency (Badan Pertanahan Nasional/BPN) in Indonesia and the Dutch Cadastre, Land Registry and Mapping Agency (Het Kadaster) in the Netherlands, two institutions historically connected through the legacy of Dutch colonial law. Using a normative juridical legal research method with statutory and conceptual approaches, this study finds that although Indonesia's land law system has been significantly influenced by the Dutch legal tradition, the two countries have developed different institutional models. The National Land Agency (BPN) remains a centralized government institution under the authority of the President of Indonesia, whereas the Dutch Kadaster has operated as an autonomous administrative body (zelfstandig bestuursorgaan) since 1994. These institutional differences have implications for the level of flexibility, accountability, and the pace of digital transformation in each organization. This article recommends strengthening the functional independence of BPN and accelerating the digitalization of land administration services as key priorities for future institutional reform.